Multifonctionnalité de l’agriculture urbaine à Montréal : étude des discours au sein du programme des jardins communautaires - Fabien Wegmuller; Éric Duchemin (VertigO)
Research show that urban agriculture could be a solution to meet modern urban issues, as food security, population health, environmental urban services, social network and popular education. However, is it the case for the cities community gardens program at Montréal (Québec, Canada) ? Based on semi-directed interviews with eleven social actors of this program, this research identifies issues about urban agriculture in Montréal. We also look the consistency between city and urban farmers discourses. Our results show a multidimensional agriculture where some functions are prioritized by actors. We also found that issues highlighted by the city (official documents) could be antagonistic of urban farmers discourses.